Implementation Of Legal Ethics And Health Professions In Improving The Quality Of Public Health Services In Indonesia - Widiyanto, Endra; Rofik Darmayanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
The application of legal ethics and the health profession is very important to improve the quality of health services in Indonesia. Not only dependent on facilities and technology, quality health services also require professional and responsible medical personnel. Good ethics in the health profession help create a fair work environment and respect patients' rights, increase public trust in the health system, and reduce harmful practices such as malpractice and discrimination. The purpose of the Implementation of Professional Ethics and Health Law is to improve the standard of health services through regulating the professional behavior of medical personnel and the implementation of services that comply with applicable laws, so as to ensure the quality and safety of patients The research method of the type of approach used in this study is normative juridical, the data source used in this study is primary legal material, legal material secondary and tertiary legal materials. Data collection techniques using literature studies including documentaries. Data analysis is normative, qualitative by interpreting and constructing statements contained in documents and legislation. In providing health services, after being diagnosed, established by a doctor or other medical personnel, drugs will be given and sometimes in providing health services medical procedures are carried out using pharmaceutical preparations and medical devices. Pharmaceutical preparations and medical devices must be safe, efficacious/beneficial, quality and affordable. The application of legal ethics and health professions in Indonesia is very important to improve the quality of health services. This ensures that medical personnel provide services that are not only professional, but also fair and respect patient rights. suggestions that can be submitted to improve the application of legal ethics and health professions in Indonesia are to strengthen professional ethics training for health workers, ensure they understand and can implement ethical values in every medical practice.